FRI0203 A SINGLE-CENTER INVESTIGATION ON THE PREVALENCE OF MALIGNANCIES IN PATIENTS WITH POLYMYALGIA RHEUMATICA AND GIANT CELL ARTERITIS BY WAY OF 18F-FDG PET/CT: A PROSPECTIVE COHORT STUDY. (2nd June 2020) - Emamifar, A.; Hess, S.; Gerke, O.; Syrak Hansen, P.; Jensen Hansen, I. M.; Marcussen, N.; Ellingsen, T.; Thye-Rønn, P.
Abstract : Background: Several chronic inflammatory diseases are associated with a higher risk of cancer.[1] Whether, this is the case in Polymyalgia Rheumatica (PMR) and Giant Cell Arteritis (GCA) is still a matter of debate. Objectives: To identify the prevalence of newly diagnosed cancers in patients with PMR and GCA by means of 18F-FDG PET/CT. Moreover, to compare the characteristics of the patients with and without cancer. Methods: Eighty consecutive patients with newly diagnosed PMR/GCA were studied. Diagnosis of PMR/GCA was confirmed by a 40-weeks follow up. A unilateral temporal artery biopsy (TAB) was also performed at the time of diagnosis. All included patients underwent an 18F-FDG PET/CT before, or in case of GCA, within 3 days of initiation of high dose oral glucocorticoid (40-75mg). All cancer-suspicious 18F-FDG-PET/CT findings were assessed thoroughly and malignant diseases were confirmed by histology. Total PMR and GCA scores were defined as the sum of a 4-point visual grading scale in each articular/periarticular site as well as arterial segment. Results: Of the 80 patients, 64 (83.1%) were diagnosed with pure PMR, 10 (13.0%) with concomitant GCA with PMR and 3 (3.9%) with pure GCA. Three patients were diagnosed with rheumatoid arthritis during follow up and excluded from the study. Five types of cancer in 4 (5.2%;95% CI:1.4-12.8%) patients were found. Two patients had breast cancer, one patient had adenocarcinoma of colon and one patient had adenocarcinoma of colon together with skin cancer. Besides, 4 (5.2%;95% CI:1.4-12.8%) patients had Monoclonal Gammopathy of Unknown Significance (MGUS). Age and C-reactive protein were significantly higher among those with solid cancers (p:0.049) and MGUS (p:0.017), respectively (Table1). Conclusion: The prevalence of cancers in this cohort was higher, compared to the 1-year prevalence of all cancer sites of 1.2% among age-, gender- and region-matched background population in 2016. Occult malignancies are important and relatively prevalent findings in newly diagnosed PMR/GCA patients. References: [1]Hemminki K, et al. Cancer risk in hospitalized rheumatoid arthritis patients. Rheumatology (Oxford) 2008;47:698-701. Disclosure of Interests: None declared